Internalization of The Values of The Qur'an and Hadith in Understanding Religious Moderation in Indonesia: Internalisasi Nilai al-Qur’an dan Hadis dalam Memahami Moderasi Beragama di Indonesia - Muhammad Mansur; Indal Abror; Mahatva Yoga Adi Pradana; Muhammad Yusup; Safutra, Lahfiz; Rizky Romdonny, Muhammad; Asrowi, Hanan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
A series of unpleasant incidents emerged with religion as the reason. Such as the destruction of the Christian cemetery (Ngrukem) in Solo, the burning of the Ahmadiyah group's mosque in Sintang, and the expulsion of Catholic students who were praying in their boarding house. This article discusses efforts to minimize intolerant incidents, that one of which is carried out through the idea of ​​moderate Islam (wasathiyah). Researchers used a qualitative approach with literature study (library research) as the main method. As a result, the Islamic values ​​of washatiyyah are an implication of the teachings of